2010
DOI: 10.1007/s12665-010-0804-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling fluoride contents of groundwater in north-central and northwestern Sri Lanka

Abstract: Chemical characterization has been made of groundwater bodies at 294 locations in four village districts in north-central and northwestern Sri Lanka, with special focus on fluorine contamination. High fluoride contents in groundwater are becoming a major problem in the dry zone of Sri Lanka, and dental fluorosis and renal failures are widespread. Field measurements of temperature, pH, and electrical conductivity were made during sampling. Chemical analyses of the water samples were later made using atomic abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…The granitic rocks with average fluoride concentration of 1939 mg/kg in Nagar Parkar area, Pakistan, contain fluoride in kaolin deposits between 468 and 1722 mg/kg and secondary kaolin deposits have 270 mg/kg which are the source of fluoride up to 7.85 mg/L in groundwater in this area (Naseem et al 2010). Studies on fluoride in groundwater in Sri Lanka carried out by Dissanayake (1991) and Young et al (2010) shows that the condition has not changed even after about two decades with fluoride above 4 mg/L in groundwater. It was found that high fluoride areas lie within low plains.…”
Section: Asian Scenariomentioning
confidence: 96%
“…The granitic rocks with average fluoride concentration of 1939 mg/kg in Nagar Parkar area, Pakistan, contain fluoride in kaolin deposits between 468 and 1722 mg/kg and secondary kaolin deposits have 270 mg/kg which are the source of fluoride up to 7.85 mg/L in groundwater in this area (Naseem et al 2010). Studies on fluoride in groundwater in Sri Lanka carried out by Dissanayake (1991) and Young et al (2010) shows that the condition has not changed even after about two decades with fluoride above 4 mg/L in groundwater. It was found that high fluoride areas lie within low plains.…”
Section: Asian Scenariomentioning
confidence: 96%
“…Studies on fluoride in groundwater in Sri Lanka carried out by Dissanayake (1991) and Young et al (2011) show Environ Chem Lett that the condition has not changed even after about two decades with fluoride above 4 mg/L in groundwater. It was found that high-fluoride areas lie within low plains.…”
Section: South Asiamentioning
confidence: 99%
“…Fluorine-bearing minerals are usually associated with acidic igneous rocks, mineralized veins and sedimentary formations (Edmunds and Smedley 2001). Its presence in felsic rocks is significantly greater than mafic and metasedimentary rocks (Young et al 2011).…”
Section: Introductionmentioning
confidence: 99%